2015
DOI: 10.1016/j.brainres.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Action-related auditory ERP attenuation: Paradigms and hypotheses

Abstract: A number studies have shown that the auditory N1 event-related potential (ERP) is attenuated when elicited by self-induced or self-generated sounds. Because N1 is a correlate of auditory feature-and event-detection, it was generally assumed that N1-attenuation reflected the cancellation of auditory re-afference, enabled by the internal forward modeling of the predictable sensory consequences of the given action. Focusing on paradigms utilizing non-speech actions, the present review summarizes recent progress o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 112 publications
10
137
0
Order By: Relevance
“…Moreover, two studies reported ERP effects prior to hand movements that were suggested to reflect preactivation of anticipated stimulus representations (Hughes & Waszak, ). Although concerns about the confounding effect of (predominantly temporal) attention have been raised for auditory studies of similar nature (Horváth, ; Lange, ; Schröger et al, ), this is not very likely for the C1, since this component was found to be insensitive to attentional modulation (Fu, Fedota, Greenwood, & Parasuraman, ; Hillyard & Anllo‐Vento, ). Thus, we argue that modulations of the C1 component in our study were due to motor‐based predictions and their consequential attenuation of visual responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two studies reported ERP effects prior to hand movements that were suggested to reflect preactivation of anticipated stimulus representations (Hughes & Waszak, ). Although concerns about the confounding effect of (predominantly temporal) attention have been raised for auditory studies of similar nature (Horváth, ; Lange, ; Schröger et al, ), this is not very likely for the C1, since this component was found to be insensitive to attentional modulation (Fu, Fedota, Greenwood, & Parasuraman, ; Hillyard & Anllo‐Vento, ). Thus, we argue that modulations of the C1 component in our study were due to motor‐based predictions and their consequential attenuation of visual responses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating action‐related auditory ERP attenuation generally assume that actions are invariant irrespective of their action effects (Horváth, ). While reproducing the well‐known N1 and P2 attenuation effects, the present experiment revealed action‐effect‐related differences in movement parameters, which is not consistent with this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory N1 component is linked to the sensory processing of acoustic information and is generated by primary auditory regions (Näätänen & Winkler, ). Its amplitude is attenuated or suppressed during auditory production (Horváth, ). Reduced N1 suppression following altered auditory feedback pitches suggests that performers may have identified the altered pitches as nonself‐generated, and then began to perceive subsequent feedback as if it were generated by an external sound source rather than by their own movements.…”
Section: Discussionmentioning
confidence: 99%
“…Neural mechanisms underlying disruptive effects of altered auditory feedback on music performance remain largely unexplored; to our knowledge, no studies in the domains of speech or music production have examined neural responses to altered pitch feedback that matches future sequence positions. We propose that the auditory N1 ERP component, elicited about 100 ms following auditory onsets, could serve as a marker for the sensory processing of altered auditory feedback during production (Horváth, ). Amplitudes of the N1 component elicited by auditory onsets are decreased when sounds are self‐generated compared to nonself‐generated in button‐pressing tasks (Aliu, Houde, & Nagarajan, ; Baess, Horváth, Jacobsen, & Schröger, ; Bendixen, SanMiguel, & Schröger, ), and self‐generated speech elicits suppressed N1 responses compared to nonself‐generated speech (Christoffels, van de Ven, Waldorp, Formisano, & Schiller, ).…”
mentioning
confidence: 99%